Comparative mRNA Expression Profiles of Riboflavin Biosynthesis Genes in Lactobacilli Isolated from Human Feces and Fermented Bamboo Shoots - Thakur, Kiran; Tomar, Sudhir K.; Wei, Zhao-Jun (Frontiers in Microbiology, 2017)
With the aim to bioprospect potent riboflavin producing lactobacilli, the present study was carried out to evaluate the relative mRNA expression of riboflavin biosynthesis genes namely Rib 1, Rib 2, Rib 3 and Rib 4 from potent riboflavin producers obtained from our previous studies. All the four genes were successfully cloned and sequenced for further analysis by in silico procedures. As studied by non-denaturing Polyacryamide gel electrophoresis, no difference in size of all the four genes among those of various lactobacilli was observed. The relative fold increase in mRNA expression in Rib 1, Rib 2, Rib 3 and Rib 4 genes has been observed to be 10 fold, 1 fold, 0.7 fold and 8.5 fold respectively. On the basis of up regulation in relative mRNA expression of all the Rib genes as well as phenotypic production attribute, KTLF1 strain was selected for expression studies in milk and whey. The fold increase in mRNA expression for all the four Rib genes was higher at 12h and 18h in milk and whey respectively. After exposure to roseoflavin, resistant variant of KTLF1 showed considerable increase in up regulation of all the targets genes. This is the first ever study to compare the mRNA expression of riboflavin biosynthesis pathway genes in lactobacilli and it also underlines the effect of media and harvesting time which significant affect the expression of rib genes. The use of roseoflavin-resistant strains capable of synthesizing riboflavin in milk and whey paves a way for an interesting and economically feasible biotechnological strategy that could be easily adapted by the food industry to develop novel riboflavin bioenriched functional foods.